IMPLANTACIÓN DE UN SISTEMA CONTABLE EN EL HOTEL ENCANTO DEL SUR, DEL CANTÓN CATAMAYO, PROVINCIA DE LOJA, PERIODO 01 DE ABRIL AL 30 DE JUNIO DEL 2017 - Collaguazo Paucar, Jessica del Carmen (2018)
The present tesis work titled "IMPLANTATION OF A COUNTABLE SYSTEM IN THE CATAMAYO'S HOTEL ENCANTO DEL SUR, LOJA PROVINCE, APRIL 1ST TO JUNE 3OTH PERIOD OF 2017", was executed with the purpose of advising the owner in the correct administration of the company; In addition to fulfilling the prerequisite to choose the Degree and Engineering Degree in Accounting and Auditing, Public Accountant-Auditor. In order to comply with the objectives set out in this thesis work, it began with the collection of information and documentation source of the hotel to be properly organized and used within the implementation of the accounting system, then the inventory was taken through the physical verification of the assets, rights and obligations that it has. Finally the accounting process was elaborated from the structuring of the plan and manual of accounts according to the activities of the establishment, continued of the elaboration of the corresponding registers like the State of Initial Situation, Daily Book, General Ledger, Balance of Verification, Worksheet , until the structuring of the Financial Statements, which reflect the real and timely information of the hotel. 5 In order to obtain the results, the relevant information related to accounting and tax aspects was first collected, starting from the general to the specific, allowing to know the current situation of the hotel, determining the different problems it faces and being able to solve them. the respective calculations of the different operations, verifying the veracity of each one of them, achieving an adequate control of the accounting process. The general conclusion reached at the end of this thesis is that the implementation of the accounting system was made to all economic activities carried out by the hotel, starting from the Initial Situation Status until obtaining the Financial Statements, informing that within the period there was a global gain of $ 468.81 US dollars during the quarter, for this reason the owner is recommended to accept the proposal as it is a viable alternative on how to properly carry Accounting in a service company and in this way have real values on the income and expenses generated by the hotel; allowing to take the respective corrections.